PENGGUNAAN METODE JARIMATIKA PADA PERKALIAN 6-10 DALAM PENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS III - Fitra, Kurniati Rezki; Yuwono, Agus; Sutopo, Yeri; Avrilianda, Decky; Subali, Bambang (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This research is motivated by the fact that students' interest in studying mathematics is still relatively minimal, because learning mathematics is still considered difficult. In the case of multiplication calculation operations, you can not only apply multiplication learning using rote memorization methods and arithmetic methods, but you can also use the finger method. By implementing the use of the Jarimatics method, it is hoped that it will have an impact on the speed and accuracy of carrying out multiplication calculation operations. The aim of the research was to determine the increase in student learning outcomes in learning through the Jarimatika method assisted by audio-visual technology media on multiplication material for class III of SD Negeri 009 Palembang. The researcher applied experimental quantitative research in research with research subjects on 19 respondents who focused on student learning outcomes. Data is obtained through activities pretest and posttest. From the results of activity research pretest resulted in an average completeness of learning outcomes of 56 and in activities posttest resulting in an average completeness learning outcome of 72. So it was concluded that students' learning outcomes in multiplication material had increased through the Jarimatika method.